Increased Opportunity to Move up the Economic Ladder? Earnings Mobility in EU: 1994-2001 - Denisa Maria Sologon; Cathal O'Donoghue (Deutsches Institut für Wirtschaftsforschung (DIW), 2009)
Do EU citizens have an increased opportunity to improve their position in the distribution of earnings over time? This question is answered by exploring short and long-term wage mobility for males across 14 EU countries between 1994 and 2001 using ECHP. Mobility is evaluated using rank measures which capture positional movements in the distribution of earnings. All countries recording an increase in cross-sectional inequality recorded also a decrease in short-term mobility. Among countries where inequality decreased, short-term mobility increased in Denmark, Spain, Ireland and UK, and decreased in Belgium, France and Ireland. Long-term mobility is higher than short-term mobility, but long-term persistency is still high in all countries. The lowest long-term mobility is found in Luxembourg followed by four clusters: first, Spain, France and Germany; second, Netherlands, and Portugal; third, UK, Italy and Austria; forth, Greece, Finland, Belgium and Ireland. The highest long-term mobility is recorded in Denmark.
Keywords: C23; D31; J31; J60; 330; Panel data; wage distribution; inequality; mobility